PENYULUHAN MASYARAKAT MELEK DIGITAL DALAM MEMBANGUN KESADARAN DAN PERLINDUNGAN HUKUM TERHADAP PENIPUAN DAN PENCURIAN DIGITAL - Sitabuana, Tundjung Herning; Sanjaya, Dixon; Shrishti (Jurnal Serina Abdimas, 2023)
Internet and social media as a result of globalization and technological revolution have become a new media in committing crime. Criminal Investigation Unit in 2022 there were 8,831 cases of cyber crime dominated by authentic data manipulation (3,723 cases) and fraud through electronic media (2,131 cases). Therefore it is necessary to have legal protection from state against security of social media as stated in Article 28C paragraph (1), Article 28F, and Article 28G paragraph (1) of the 1945 Constitution. Community service activities conducted to the people of RT.001/RW.006, Srengseng Village, Kembangan District, West Jakarta, with theme of digital literacy community to build awareness and legal protection against fraud and digital theft. This activity is in the form of legal counseling, with pre-survey stages, socialization, and monitoring and evaluation. This location was chosen because the community was a legal awareness group need to increase public understanding of digital security. The results achieved of legal counseling are the community to know the scope, form, type, mode, and workings of fraud and digital theft, know legal aspects and protection available, as well as efforts that need to be made to avoid fraud and theft digital so that people are expected to be able to literate on digital security. Suggestions to the government to increase socialization concerning institutions that handle fraud and digital theft, and scope of socialization needs to be expanded to increase digital literacy and legal awareness of community.